Analisis Kemandirian dan Efektivitas Keuangan Pada Kinerja Pemerintah Kota Medan - Junita Putri Rajana Harahap; Murni Dahlena Nasution (Jurnal Administrasi Bisnis, 2019)
Performance is the output of activities / programs that have been planned in connection with the use of the budget with measurable quantity and quality. Implementation of performance is said to be good if the achievement is in accordance with what has been planned. Performance measurement is related to autonomy which requires the authority and responsibility of the local government in managing finances and running its government. Good performance can be measured by several ratios, namely the independence ratio and effectiveness of PAD, which was used in this study. This study aims to find out and analyze how the Medan city government in organizing its government in order to realize the interests of the community based on the principles of transparency and public accountability. This study uses descriptive analysis and uses quantitative and qualitative data with primary and secondary data sources. This research was conducted in the city government of Medan with years of research starting from 2012 to 2016. The results of this study indicate that the city government of Medan has been very independent and very effective in the performance of financial management and running the wheels of government.